2010
DOI: 10.1097/mpg.0b013e3181aed6f1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome After Percutaneous Endoscopic Gastrostomy in Children and Young Adults

Abstract: Preoperative diagnosis, indication, prematurity, and neurological impairment did not influence postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
74
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 23 publications
13
74
0
9
Order By: Relevance
“…When the distribution of 34 patients included in this study was examined, it was observed that the patients with neurological problems were in the first order. This was compatible with the large series published worldwide (8,9). In two studies conducted in our country, it was reported that children with neurological diseases were in the first order among the pediatric subjects in whom PEG was placed (4,10).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…When the distribution of 34 patients included in this study was examined, it was observed that the patients with neurological problems were in the first order. This was compatible with the large series published worldwide (8,9). In two studies conducted in our country, it was reported that children with neurological diseases were in the first order among the pediatric subjects in whom PEG was placed (4,10).…”
Section: Discussionsupporting
confidence: 76%
“…In a study which included 747 children which is the largest series so far, the rate of early postoperative complication (wound infection, pneumoperitoneum, tissue necrosis and most importantly separation of the stomach from the abdominal wall) was found to be 4% (8). The rate of minor complications including wound infection and formation of granuloma after discharge was found to be 20% and gastrocolonic fistula was reported only in one patient (8). In our series, local stoma infection which developed as a result of placement of PEG was observed in 8,8% of the subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Известно лишь, что в США ежегодно у педиатрических пациентов выполняется около 11 000 чрескожных эндоскопических гастро-стомий [19][20][21]. Данные о частоте использовании лапароскопической гастростомии разрозненны.…”
Section: дискуссияunclassified
“…Чрескожная эндо-скопическая гастростомия, в отличие от традиционной, способствует более быстрому восстановлению состояния ребенка с наименьшими болевыми ощущениями [30,31]. Ее выполняют два врача: один проводит эндоскопиче-скую процедуру, второй -хирургические манипуляции.…”
Section: обмен опытомunclassified